KOMBINASI KOTORAN AYAM DAN KOTORAN KERBAU YANG DIFERMENTASI TERHADAP PERTUMBUHAN DAN PRODUKSI PADA MAGGOT (Hermetia illucens) - T. Iskandar Johan; Aldi Fahrizal; Fakhrunas M.A. Jabbar (DINAMIKA PERTANIAN, 2021)
The purpose of this study was to determine the effect of the combination of chicken manure and buffalo manure on the growth and production of maggot and to determine the percentage of the best combination of chicken manure and buffalo dung on the growth and production of maggot. This study used a completely randomized design with five treatments and three replications, consisting of treatments P1: Chicken Manure (100%), P2: Buffalo Manure (25%) + Chicken Manure (75%), P3: Buffalo Manure (50%) + Chicken Manure (50%), P4: Buffalo Manure (75%) + Chicken Manure (25%), and P5: Buffalo Manure (100%). The results showed that the best treatment was found on P2: Buffalo Manure (25%) + Chicken Manure (75%) with maggot weight growth of P2 0.143 g, maggot length growth of 1.49 cm, maggot daily growth rate of 1.02%, and 93.00 gr for maggot production.